Investigation of the performance of the Kaiser-Hamming window in design of QMF bank - Kamislioglu, Bircan; Karaboga, Nurhan (Pamukkale Univ, 2019)
In recent years, significant improvements have been in fast digital filters and filter banks. QMF (Quadrature Mirror Filter) bank, known as an application of multi-speed filter banks are widely used sub-band coding, image compression, word coding, biomedical signal processing and communication systems. In this study; QMF bank design is realized via a windowing method with prototype FIR (Finite Impulse Response) filter design and based on cascade bounded Kaiser and Hamming windows for eliminating undesired oscillations in QMF bank design. It has been investigated how the performance changed of the filter degree in designing filter with different window functions and at the result it is shown that Kaiser-Hamming window with lower stopband attenuation could be used in QMF bank design.
Keywords: FIR QMF bank; Windowing; Kaiser window; Hamming window; Kaiser-Hamming window